Establishment of Burn First Aid Laypersons with Beg-Teg in SMPN 1 Kalisat - Darotin, Rida; Nastiti, Eky Madyaning; Ekaprasetia, Feri; Wulansari, Yunita Wahyu; Wirasakti, Guruh (Blambangan Journal of Community Services (BJCS), 2025)
Introduction: Burns are the main cause of crisis conditions and major traumatic injuries that risk causing various problems, resulting in tissue death. Burns are injuries that occur to skin tissue or other tissues caused by radioactivity, the flow of electric current, friction of hot objects, or exposure to chemicals. Burns that occur in children are a vital health problem but have not been widely disclosed compared to adults. Thermal burns are most common in children, either due to fire or hot water. Children are an age group that is vulnerable to injury in connection with curiosity about their surroundings. One of the injuries that often occur in school-age children is burns. The results of the situation analysis and discussion with partners formulated one problem, namely: lack of information, knowledge and understanding related to first aid problems in student groups in schools, especially in the provision of first aid (First Aid) for burns, the proposer offered through PKM in the Formation of Layperson First Aid for Burn Cases with TEG-BEG (Technological Gadgets on Based Emergency Group). Methode: First Aid Burns using TEG-BEG is a collection of several educational media based on research results from PKM proposers together with proposer members who have been published. Kopdar Banget's learning media consists of Power Point Media, documentary short films, FAG (First Aid Guideline), and EFA-Game (Education First Aid Game). In this PKM activity, the school as a partner participates in the implementation of the program through the provision of human resources, namely students and teachers in this activity. In addition, the school will also be involved in providing support for the provision of places and the implementation of PKM program activity times. At the end of the PKM program, evaluation and sustainability of the program in the field will be carried out after the activities are completed through supervision and reevaluation of activities. Resulth: There are differences in knowledge in students after providing education using several educational media platforms. Conclusion: The PKM TEG-BEG activity can increase the knowledge of SMPN 1 Kalisat students. This is evidenced by improving the graph of knowledge level. This is supported by the existence of fun educational media and following technological developments in accordance with the target of PKM.